2020
DOI: 10.5937/afmnai2004387d
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to maggot therapy for healing of diabetic foot ulcers

Abstract: The use of maggot therapy (MT) is proving effective in the treatment of complicated diabetic foot ulcers (DFUs). Most of the previous studies have focused on the comparison of MT and routine treatment approaches for the management of DFUs. The aim of this study was to add MT to routine treatment line of DFUs as a new approach. In this study, the principal expectation from MT method was to prepare wound bed for continuation of the treatment with other measures. This study was designed as a before-after observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In a clinical trial, Malekian et al concluded that MDT using sterile maggots of L. sericata is a safe and effective method for treating the DFUs infected with Staphylococcus aureus and Pseudomonas aeruginosa [10] , which is consistent with our results. Siavash et al and Dehghan et al also revealed that MDT, as a new treatment approach, is effective in treating atypical DFUs that are refractory to conventional therapies [17] , [3] . In line with the results of our study, Mirabzadeh et al showed the MDT as an acceptable and easy-to-use method for the treatment of complicated and extensive DFUs [18] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a clinical trial, Malekian et al concluded that MDT using sterile maggots of L. sericata is a safe and effective method for treating the DFUs infected with Staphylococcus aureus and Pseudomonas aeruginosa [10] , which is consistent with our results. Siavash et al and Dehghan et al also revealed that MDT, as a new treatment approach, is effective in treating atypical DFUs that are refractory to conventional therapies [17] , [3] . In line with the results of our study, Mirabzadeh et al showed the MDT as an acceptable and easy-to-use method for the treatment of complicated and extensive DFUs [18] .…”
Section: Discussionmentioning
confidence: 99%
“…DFU can lead to infection, gangrene, necrosis, and skin defects in all layers from the distal to proximal areas of the body [2] . DFU can be caused by a defective healing process resulting from intrinsic (neuropathy, vascular disorders, and other systemic effects of diabetes) and extrinsic factors (wound infection, callus formation, and high-pressure injection) [3] . Approximately 20% of patients with diabetes refer to the medical centers with the chief complaint of DFU [2] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations